An Aboriginal Worldview of Helping: Empowering Approaches - Poonwassie, Anne; Charter, Ann (Canadian Journal of Counselling and Psychotherapy, 2007)
Euro-Canadian interventions have not successfully addressed the socio-economic problems experienced in Aboriginal communities as a result of years of colonization. Leading up to the new millennium, cultural forces have started to shift, and Euro-Canadian counsellors, therapists, and other helpers began to respond more effectively to the needs of Aboriginal peoples. A number of Aboriginal groups and communities took leadership by developing their own holistic approaches to healing/wellness, based on their worldviews. A reflection on this process with an awareness of Aboriginal worldviews and cultural imperatives offers possible approaches which facilitate empowerment in working with Aboriginal communities and Aboriginal clients.